Hubungan Penggunaan Backpack dengan Keluhan Nyeri Bahu pada Siswa di SDN Barusari 01 Semarang - Syurrahmi Syurrahmi; Lilik Sigit Wibisono; Zamroni Zamroni; Putri Soniatus; Almita Ratu Rifanda (Lembaga Pengembangan Kinerja Dosen, 2024)
One of the health problems involving school-aged children is musculoskeletal complaints which are thought to be caused by using backpacks that are too heavy. School bags are used as containers for books and other school equipment to be taken to school. The current trend is that schools often give homework, assignments and extra-curricular activities which have an impact on the amount of material that school students have to bring. Objective: To determine the differences in levels of neck pain when using backpacks in children aged 10 - 12 years among students at SDN Barusari 01 Semarang in terms of gender. The sample in this study consisted of 52 children. Research Method: backpack use questionnaire and REBA (Rapid Entire Body Assessment) observation sheet. This research uses bivariate analysis, namely the Chi-Square test. The results showed that, of the 52 students, 26 students (68.2%) complained of mild pain and 18 students complained of moderate pain (21.7%) and 8 students did not complain of pain (10.10%). There is a relationship between backpack use and complaints of shoulder pain with a P value of 0.011 (P<0.05). Conclusion: There is a relationship between the use of backpacks and complaints of shoulder pain in students at Sdn Barusari 01 Semarang. Suggestion: Awareness of paying attention to the load or weight of backpacks at school is important to implement as a preventive measure to reduce the incidence of complaints of shoulder pain in school-aged children.